P7-004 Histamine inhibits differentiation of skin fibroblasts into myofibroblasts - 山岡, 邦宏; 田中, 良哉; 山形, 熏; 中野, 和久; 林, 琳; 中山田, 真吾; 澤向, 範文 (Japanese Journal of Clinical Immunology, 2014)
【Background】Histamine (HA) and TGF-β, major mediators secreted by mast cells are involved in skin inflammation and systemic sclerosis. However, it remains largely unclear how the respective signaling are integrated to achieve development of skin fibrosis. 【Objectives】Investigate the effect of HA signaling during myofibroblasts differentiation. 【Methods】Skin fibroblasts (SFBs) were stimulated with TGF-β, HA, or HA receptor antagonists. Expression of α smooth muscle actin (αSMA), HA receptors, and Smads were analyzed at mRNA and protein. 【Results】Expression of H1-receptor (H1R) and H2-receptor (H2R) were detectable in SFBs at both mRNA and protein level. Interestingly, addition of HA inhibited αSMA expression induced by TGF-β which was antagonized by H1R antagonist but not H2R antagonist. Correspondingly, phosphorylated Smad2 was induced by TGF-β stimulation whereas inhibited its phosphorylation after HA treatment. 【Conclusions】HA inhibited differentiation of SFBs into myofibroblast induced by TGF-β in a H1R dependent manner, which emphasized the cirtical functions of H1R in the development of skin fibrosis. Thus, H1R may be a therapeutic target for skin fibrosis.